On the Interaction of β-Amyloid Peptides and α7-Nicotinic Acetylcholine Receptors in Alzheimer’s Disease - Oz, Murat; E. Lorke, Dietrich; S. Yang, Keun-Hang; Petroianu, Georg (Current Alzheimer Research, 2013)
Deterioration of the cortical cholinergic system is a leading neurochemical feature of Alzheimer’s Disease (AD). This review summarizes evidence that the homomeric α7- nicotinic acetylcholine receptor (nAChR) plays a crucial role in the pathogenesis of this disease, which is characterized by amyloid-β (Aβ) accumulations and neurofibrillary tangles originating from of hyperphosphorylated tau protein. Aβ binds to α7-nAChRs with a high affinity, either activating or inhibiting this receptor in a concentration-dependent manner. There is strong evidence that α7-nAChRs are neuroprotective, reducing Aβ-induced toxicity; but co-localization of α7- nAChRs, Aβ and amyloid plaques also points to neurodegenerative actions. Aβ induces tau phosphorylation via α7-nAChR activation. Aβ influences hippocampus-dependent memory and long-term potentiation in a dose-dependent way: there is evidence that enhancement by picomolar Aβ concentrations is mediated by α7-nAChRs, whereas inhibition by nanomolar concentrations is independent of nAChRs and probably mediated by small Aβ42 oligomers. α7-nAChRs located on vascular smooth muscle cells and astrocytes are also involved in the pathogenesis of AD. Although these data strongly point to an important role of α7-nAChRs in the development of AD, dose-dependence of the effects, rapid desensitization of the receptor and dependence of the effects on Aβ aggregation (monomers, oligomers, fibrils) make it difficult to develop simple therapeutic strategies acting upon this receptor.
Keywords: tau phosphorylation